2014
DOI: 10.5194/hessd-11-3675-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil erosion by snow gliding – a first quantification attempt in a sub-alpine area, Switzerland

Abstract: Abstract. Snow processes might be one important driver of soil erosion in Alpine grasslands and thus the unknown variable when erosion modelling is attempted. The aim of this study is to assess the importance of snow gliding as soil erosion agent for four different land use/land cover types in a sub-alpine area in Switzerland. We used three different approaches to estimate soil erosion rates: sediment yield measurements in snow glide deposits, the fallout radionuclide 137Cs, and modelling with the Revised Univ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In the Alps, shallow erosion on grassland is a widespread phenomenon (Wiegand & Geitner 2010;Meusburger & Alewell 2014;Geitner et al 2021). In recent decades, some areas experienced increased rates of shallow erosion.…”
Section: Introductionmentioning
confidence: 99%
“…In the Alps, shallow erosion on grassland is a widespread phenomenon (Wiegand & Geitner 2010;Meusburger & Alewell 2014;Geitner et al 2021). In recent decades, some areas experienced increased rates of shallow erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Complex soil profile morphologies may occur along an avalanche path with both buried and truncated soil horizons. Snow gliding phenomena can contribute significantly to soil erosion at the snow-soil interface as shown by Meusburger et al (2014), who identified snow gliding as a relevant driver for winter soil erosion in the Swiss Alps. Despite the first try by Konz et al (2009) at including a winter factor in the RUSLE, the incidence of snow-induced erosion on large scales (e.g., catchment or avalanche areas) cannot be evaluated with a well-defined standard procedure.…”
mentioning
confidence: 99%